Highly diverged novel subunit composition of apicomplexan F-type ATP synthase identified from Toxoplasma gondii - Salunke, Rahul; Mourier, Tobias; Banerjee, Manidipa; Pain, Arnab; Shanmugam, Dhanasekaran (Plos Biology, 2018)
The mitochondrial F-type ATP synthase, a multisubunit nanomotor, is critical for maintaining cellular ATP levels. In T. gondii and other apicomplexan parasites, many subunit components necessary for proper assembly and functioning of this enzyme appear to be missing. Here, we report the identification of 20 novel subunits of T. gondii F-type ATP synthase from mass spectrometry analysis of partially purified monomeric (approximately 600 kDa) and dimeric (> 1 MDa) forms of the enzyme. Despite extreme sequence diversification, key F-O subunits a, b, and d can be identified from conserved structural features. Orthologs for these proteins are restricted to apicomplexan, chromerid, and dinoflagellate species. Interestingly, their absence in ciliates indicates a major diversion, with respect to subunit composition of this enzyme, within the alveolate clade. Discovery of these highly diversified novel components of the apicomplexan F-type ATP synthase complex could facilitate the development of novel antiparasitic agents. Structural and functional characterization of this unusual enzyme complex will advance our fundamental understanding of energy metabolism in apicomplexan species.